Fascia Iliaca Compartment Block as Pain Management for Postoperative Femur Fracture in the Elderly: A Case Report - Utama, Sigit Prasetya; Yuliana, Friskha; Kuntoadi, Danang (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: Femur fractures are most common in geriatric patients, necessitating careful consideration of perioperative medications. Effective pain management is crucial to minimize neurohormonal stress responses. Reducing opioid use in older patients can prevent side effects and complications. The fascia iliaca compartment block (FICB) is a safe and efficient nerve block method, known to decrease opioid needs in hip surgery. It is anticipated to enhance mobilization speed and ambulation and reduce postoperative nausea, vomiting, deep vein thrombosis (DVT), and pneumonia, thereby improving overall outcomes for geriatric patients undergoing hip surgery.Case: A 71-year-old female with a closed right intertrochanteric femur fracture underwent open reduction and internal fixation with a proximal femoral nail antirotation. Classified as ASA II, geriatric, with stage I hypertension, her preoperative vital signs included a blood pressure of 170/95 mmHg, heart rate of 65 beats per minute, respiration rate of 20 times per minute, and SpO2 of 98% with nasal cannula oxygen at 3 lpm. Spinal anesthesia was administered at L3-L4, and an FICB was performed postoperatively. Pain assessment, rescue analgesic use, and postoperative nausea were evaluated post-surgery, with monitoring at 6, 24, and 48 hours.Discussion: Pain management with regional FICB anesthesia can simultaneously block the femoral nerve, obturator nerve, and lateral femoral cutaneous nerve. Thus, minimizing systemic symptoms compared to analgesics administered intravenously. In this case, the administration of 30 cc of levobupivacaine via a FICB provided effective analgesia for up to 72 hours post-blockade in a geriatric patient without causing side effects, such as postoperative nausea.Conclusion: Postoperative FICB for hip surgery in geriatric patients provides effective analgesia with minimal side effects.